PENGARUH KEKHAWATIRAN PRIVASI NIAT UNTUK MENERIMA IZIN APLIKASI PADA PENGGUNA MOBILE MAHASISWA BATAM - Alvi Geovanny; Infrisanti Wilson Tong; Jason Aaron Yang; Vincent Octarian Vianto (Universitas Negeri Padang, 2021)
Mobile usage has become a part of our daily lives. However, many mobile users ignore the existence of app permissions in an app. One of the reasons is the lack of information related to app permissions. If users are not careful, app permissions can be abused by hackers to steal their data such as SMS, photos, microphone access, and GPS. The purpose of this study is to observe the perspective of university students in Batam regarding app permissions as well as to see the consequences of that perspective. The basis of this research is using survey method for 132 social media users and regression. This study proves that mobile users’ information privacy concerns have an influence on the intention to accept app permissions, which means that university students of Batam tend to consider personal information privacy on mobile before accepting app permissions. However, computer anxiety and perceived control do not affect mobile users’ information privacy concerns, which means university students of Batam have neither computer anxiety nor perceived control over personal information privacy on mobile.